The efficiency and efficacy of tranexamic acid in prevention of blood loss during or after caesarean delivery: a comparative study - Raina, Supriya; Suguna, V.; Prabraju, Padmaja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The practice of caesarean section is increasing day by day. Delivery by caesarean section can cause more complications than normal vaginal delivery and one of the most common complications is primary or secondary postpartum hemorrhage. The aim of present study was to study the efficacy and safety of tranexamic acid in reducing blood loss during and after caesarean section. Methods: This study was conducted at Deccan College of Medical Sciences, Hyderabad. It was a prospective randomized double blind placebo controlled study. This study includes 60 pregnant women divided in to two groups. Just before the induction of anesthesia 1 gm of tranexamic acid in 20 ml of normal saline was given over 10 minutes in test group and 20 ml of normal saline was infused in control group. Results: The demographic characters of patients in two groups were comparable. There was no statistically significant difference in the heart rates, respiratory rates and blood pressures in the two groups. There was statistically significant difference in the quantity of the blood loss from during the operation and 2 hours postpartum (p=0.003). Total mean blood loss in control group was 718.80±233.1 ml and in study group was 554.28±207.8 ml. The drop in hemoglobin after caesarean section in study group was not significant where as in control group was significant. There was no significant difference in the prothrombin time and partial thromboplastin time in the groups, pre and post operatively. In this study the use of tranexamic acid reduced the dose of other uterotonics like syntocin in study group. Conclusions: Tranexamic acid significantly reduced the amount of blood loss during the caesarean section and also reduced the use of other uterotonics. Thus, tranexamic acid can be used safely and effectively in subjects undergoing caesarean section.